Usefulness of biodegradable polydioxanone stents in the treatment of postsurgical colorectal strictures and fistulas - Pérez Roldán, F.; González Carro, P.; Villafáñez García, M. C.; Aoufi Rabih, S.; Legaz Huidobro, M. L.; Sánchez-Manjavacas Múñoz, N.; Roncero García-Escribano, O.; Ynfante Ferrús, M.; Bernardos Martín, E.; Ruiz Carrillo, F. (Endoscopy, 2012)
Benign colonic strictures and fistulas are a growing problem presenting most commonly after bowel resection. Standard treatment is with endoscopic bougies or, more usually, balloon dilation. When these approaches are not successful, other solutions are available and different endoscopic and surgical approaches have been used to treat fistulas. We present an additional option – biodegradable stents – for the treatment of colonic strictures and fistulas that have proven refractory to other endoscopic interventions. We analyzed the results from 10 patients with either a postsurgical colorectal stricture (n = 7) or rectocutaneous fistula (n = 3) treated with the biodegradable SX-ELLA esophageal stent (covered or uncovered). Stents were successfully placed in nine patients, although early migration subsequently occurred in one. Placement was impossible in one patient due to deformity of the area and the fact that the stricture was approximately 30 cm from the anus. The fistulas were successfully closed in all patients, although symptoms reappeared in one patient. In the six patients who received stents for strictures, symptoms resolved in five; in the remaining patient, the stent migrated shortly after the endoscopy. Treatment of colonic strictures and rectocutaneous fistulas with biodegradable stents is an effective alternative in the short-to-medium term. The stent does not have to be removed and is subject to very few complications. The drawbacks of this approach are the need to repeat the procedure in some patients and the lack of published series on efficacy.